Nutritional Characteristic of Pregnant Women at the Hospital Nacional Dos de Mayo - Pajuelo Ramírez, Jaime (1997)
It was studied 259 pregnant women corresponding to I (45), II (88) and III (126) trimesters, being 56 adolescent. The nutritional assessment was made from an anthropometic and biochemical point of view. The following measures were taken: weight, height, brachial perimeter (AP) and triceps skinfold thickness (TST); with the first two the Quetelet Index (IQ) was calculated and with the latter ones the muscular area (MA) and fat area (FA). Biochemically the hemoglobin (Hb) and hematocrite (Ht) was dosed; those women under 11 g/dl were considered anemics.Most pregnant have IQ within normal levels for non-pregnant reference. Remaining pregnant prevails overweight and obesity of temporal type. In deposit ratios occurs something similar to the IQ, with the difference that deficit predominates.Sixty percent are anemic, 33,65 and 66%, corresponding to the I, II and III trimesters of pregnancy, respectively. 72% of the population did not Intake any supplementation. 69% of pregnant women of II and III quarter did not receive any supplementation. We conclude that the problem of pregnant women is anemia, and in less degree, overweight and obesity.